PO203 Assessing disease activity and cardiac involvement in myositis. (1st December 2017) - Lilleker, James B; Guy, Mark; Roberts, Mark E; Sergeant, Jamie C; Cooper, Robert G; Chinoy, Hector
Abstract : Background: Methods of monitoring disease activity and detecting cardiac involvement in myositis are inadequate, contributing to poor outcomes. We investigated the potential for a panel of serum muscle damage markers to address these issues. Methods: Disease activity and cardiac involvement in adult myositis patients was assessed and serum total creatine kinase (CK), cardiac troponin-T (cTnT), cardiac troponin-I (cTnI) and CK-MB were measured. Convergent construct validity assessment using Spearman's ranked correlation and logistic regression were used. Results: Of 46 patients, most had dermatomyositis (39%). The mean age was 52 years. 72% were female. Strongest correlations were observed between cTnT and manual muscle testing scores (rho −0.53, p<0.001), and between CK-MB and the Health Assessment Questionnaire (HAQ) (rho 0.44, p=0.002). Combining an abnormal CK and CK-MB identified a group with a significantly higher HAQ (OR 2.06, 95% CI 1.07–3.97, p=0.031), whereas this was not found in those with an abnormal CK alone. Serum muscle damage marker levels were not significantly different in those with cardiac involvement (n=8) although an abnormal cTnI had 95% specificity for cardiac involvement. Conclusion: When assessing disease activity in myositis, serum cTnT and CK-MB appear useful in addition to total CK, whereas cTnI may assist identification of cardiac involvement.